2020
DOI: 10.3390/ijms21197261
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Structure and Dynamics of the Ca2+-ATPase Bound to Phosphorylated Phospholamban

Abstract: Sarcoplasmic reticulum Ca2+-ATPase (SERCA) and phospholamban (PLB) are essential components of the cardiac Ca2+ transport machinery. PLB phosphorylation at residue Ser16 (pSer16) enhances SERCA activity in the heart via an unknown structural mechanism. Here, we report a fully atomistic model of SERCA bound to phosphorylated PLB and study its structural dynamics on the microsecond time scale using all-atom molecular dynamics simulations in an explicit lipid bilayer and water environment. The unstructured N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…In addition, oligomeric PLB is mainly palmitoylated while monomeric PLB is much less so 16 . PLB phosphorylation results in a release of SERCA1a inhibition without its full dissociation from the pump 14 . All these data on PLB could suggest that the same kind of interplay between SLN oligomerisation, palmitoylation and phosphorylation for inhibition of SERCA1a is present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oligomeric PLB is mainly palmitoylated while monomeric PLB is much less so 16 . PLB phosphorylation results in a release of SERCA1a inhibition without its full dissociation from the pump 14 . All these data on PLB could suggest that the same kind of interplay between SLN oligomerisation, palmitoylation and phosphorylation for inhibition of SERCA1a is present.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PLB and SLN undergo post-translational modifications. Residues in their N-terminus are target for kinases and phosphorylation affects association with the pump 12 14 . Consequently, phosphorylation of residues localized in PLB or SLN N-termini seems to be important for association to SERCA isoforms in the groove as illustrated by molecular models 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The angle between E 2P ( E 2·BeF 3 − ) and E 1Ca 2 was calculated 56.4°, 51.0°, 53.0°, and 54.8° from structures of 3B9B 2 for E 2·BeF 3 − and 1SU4 6 , 2C9M 52 , 3J7T 53 , and 5XA7 54 for E 1Ca 2 , respectively. Note that 1SU4 6 , 2C9M 52 , 3J7T 53 , and 5XA7 54 were categorized E 1Ca 2 state in Ref 55 . The angle between E 1PCa 2 ( E 1Ca 2 ·AlF 4 − ·ADP) and E 2P ( E 2·BeF 3 − ) was calculated 58.8° from structures: (PDB ID code: 1T5T 56 and 2ZBE 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, pharmacological stimulation of SERCA2a activity has been proposed as a therapeutic strategy to improve cardiac function 10 13 . There is extensive evidence indicating that key effector sites are localized in the transmembrane domain of the pump, including regulatory and inhibitory binding sites 14 . More recently, we have shown that the membrane protein dwarf open reading frame (DWORF) binds to the transmembrane domain of SERCA2a and directly stimulates the activity of the pump 15 .…”
Section: Introductionmentioning
confidence: 99%